Penerapan Jigsaw Learning Dalam Riset Aksi Partisipatoris - M.Saifuddin, M.Saifuddin M.Saifuddin (BINA' AL-UMMAH, 2017)
AbstractThe learning outcomes of Participatory Action Research lecture semester VI The Department of Islamic Community Development, Faculty of Da'wah and Communication Studies, UIN Raden Intan Lampung in the previous year showed the low ability of students, especially on the subject matter of participatory planning. This is due to the ability of understanding and low student skills, is a new material, as well as the model or lecture approach used by lecturers has not been optimal. Therefore the problem raised in this research is "Whether with the application of cooperative learning model (STAD type), the quality of Participatory Action Research lectures can be improved?"The classroom action research in this study was carried out in two cycles. The data were collected using test and observation techniques. Measuring the success of the action is if the average formative test score of students is more than or equal to 70 and complete the classical study at least 75%, the value of student learning activities and lecturer perfomansi value of at least 70 or B.After the application of cooperative learning model in cycle I obtained the average score of 71.2 students and 66.70% complete classical learning. In the second cycle student learning outcomes increased with the average score of 75.6 and complete learning classical reach 80.00%. Student learning activity in cycle I reaches 77,5 or B and in cycle II increased to 86,25 or A. Lecturer's perfomance, in cycle I get value 78,75 or A and in cycle II to 86,25 or A. Result this has been considered sufficient, because each component (learning outcomes, student learning activities, and lecturer's perfomansi) meets the benchmarks of successful actions in the form of cooperative learning model.Thus, it can be concluded that through the cooperative learning model (STAD type), the quality of the Participatory Action Research lectures on the Islamic Community Development Department can be improved. Therefore, it is suggested that lecturers who have participatory action research, especially Participatory Planning materials can use cooperative learning model as an option.Kata Kunci : Participatory action research, cooperative learning model